(untitled) (Revista de Ciências Agroveterinárias, 2024)
The present study aimed to investigate the relationship that different actors involved in family farming, residing in a Quilombola community in the municipality of Paulistana - Piauí, establish with agricultural activities. Thus, a field study was conducted to carry out interviews with a semi-structured questionnaire, containing objective and subjective questions. The majority (76.47%) of respondents were female, aged between 18 and 30 years old, most of whom had incomplete primary education and had an income of up to 1 minimum wage. 84.22% of respondents confirmed that their children contribute to agricultural activities. 7 teenagers were identified, between 12 and 18 years old. 70.58% of adolescents reported carrying out agricultural and non-agricultural activities on the family property. Regarding the intention to stay or escape from the rural environment, 64.70% stated that they intend to migrate to the urban area of the city, in order to study or seek better job opportunities. 92.31% of women responded that they felt valued by society and entities linked to family farming. In turn, 87.5% of the elderly reported having a health problem, including back pain and high blood pressure. Therefore, the number of children carrying out agricultural activities in the rural community is significant and, due to the lack of work and study opportunities, there is a high proportion of young people who do not wish to remain in the community. Furthermore, women play an important role in the context of family farming, actively participating in the various activities within the property and the rural community, just as the elderly farming population demonstrates health problems related to their work activities.